Xenocentrism and consumer buying behavior: A comparative analysis of Malaysian vs. Nigerian consumers - Vimala Venugopal; Mário Nuno Mata; Chiemelie Benneth Iloka; Rui D. Dantas; Anabela Batista; Jo\~ao Xavier Rita; José Moleiro Martins (Journal of Risk and Financial Management, 2022)
Across the globe, xenocentrism has emerged as a critical concept for understanding the behavior of consumers towards the purchase of local and foreign products. In line with this context, and based on samples collected from Malaysia and Nigeria, this study analyzed the direct effects of xenocentrism on the buying behavior of consumers towards imported products with perceived product quality, purchase intention, and product attitude as the variables used to measure consumers' buying behavior. XSCALE was used to measure xenocentrism, and the research model was analyzed with the partial least squares form of structural equation modeling. A total of 400 responses were gathered from Malaysia, whereas 453 responses were gathered from Nigeria. Findings from the investigation show that xenocentrism has a positive influence on perceived product quality (Malaysia = 46.7%, Nigeria = 35%), purchase intention (Malaysia = 46%, Nigeria = 47.3%), and product attitude (Malaysia = 39.2%, Nigeria = 38.4%), Based on these findings, this study concluded that xenocentrism is a valid construct for assessing the purchase behavior of consumers in Malaysia and Nigeria towards foreign products competing in their local markets. On the same note, the findings from this research can be used to develop sustainable marketing strategies suitable for xenocentric consumers across Malaysia and Nigeria (in particular), and the entire developing economies (in general).
Keywords: M300; M310; 330; attitude; behavior; consumer; products; purchase intention; xenocentrism; AMOS-SEM